Uniqueness theorem for sequences of piecewise polynomial functions - Karen Keryan (National Academy of Sciences of Armenia)
In the paper sequences of piecewise polynomial functions are considered, where each of the function is the projection of subsequent ones. A reconstruction theorem is proved for such sequences converging in measure from its limit if the majorant of the sequence satisfies some condition.
Keywords: Mathematics; Fourier analysis